2009
DOI: 10.1002/chin.200912047
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: An Efficient One‐Pot Synthesis of β‐Amino/β‐Acetamido Carbonyl Compounds via ZrCl4‐Catalyzed Mannich‐Type Reaction.

Abstract: Multicomponent reactions O 0359An Efficient One-Pot Synthesis of β-Amino/β-Acetamido Carbonyl Compounds via ZrCl 4 -Catalyzed Mannich-Type Reaction. -ZrCl 4 is an efficient catalyst for the three-component reaction of carbonyl compounds (I), aromatic aldehydes (II), and aromatic primary amine (III) and for the four-component reaction of, aromatic aldehydes (V), acetyl chloride, and acetonitrile (VI). -(SANJEEVA REDDY*, C.; PURNACHANDRA REDDY, G.; Chin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Its products (Mannich bases) are of considerable importance in industry, natural products, chemistry, and pharmacy (Azend et al , 1998 ). A large number of studies on the Mannich-type reactions have been reported (Gu et al , 2008 ;Uraguchi et al , 2008 ;Bayrak et al , 2009 ;Candeias et al , 2009 ;Hong et al , 2009 ;Odedra and Seeberger , 2009 ) with many methods utilizing Lewis acids (Ollevier and Nadeau , 2007 ;Stas and Tehrani , 2007 ;Wang et al , 2007b ;Wu et al , 2007b ;Ramalingam and Kumar , 2008 ;Sanjeeva and Purnachandra , 2008 ;Chen et al , 2009 ), Bronsted acids (Guo et al, 2007;Rueping et al, 2007;Yamanaka et al, 2007), solid acids (Bigdeli et al , 2007 ;Li et al , 2007 ;Wang et al , 2007a,c ;Reddy et al , 2008 ), bases (Chandler et al , 2009 ;Wu et al , 2009 ), metal complexes (Wu et al , 2007a ;Wieland et al , 2009 ), ionic liquids (Dong et al , 2007 ;Fang et al , 2009 ), inorganic salts (Aryanasab and Saidi , 2008 ;Kidwai et al , 2008 ), and organic compounds (Verkade et al , 2008 ;Kano et al , 2009 ) as catalysts and many volatile organic solvents, some of which are hazardous for the environment. There are few reports on the use of heteroarylamines as substrates in the Mannich-type reactions (Shaabani et al , 2007 ;Hao et al , 2009 ).…”
Section: Introductionmentioning
confidence: 98%
“…Its products (Mannich bases) are of considerable importance in industry, natural products, chemistry, and pharmacy (Azend et al , 1998 ). A large number of studies on the Mannich-type reactions have been reported (Gu et al , 2008 ;Uraguchi et al , 2008 ;Bayrak et al , 2009 ;Candeias et al , 2009 ;Hong et al , 2009 ;Odedra and Seeberger , 2009 ) with many methods utilizing Lewis acids (Ollevier and Nadeau , 2007 ;Stas and Tehrani , 2007 ;Wang et al , 2007b ;Wu et al , 2007b ;Ramalingam and Kumar , 2008 ;Sanjeeva and Purnachandra , 2008 ;Chen et al , 2009 ), Bronsted acids (Guo et al, 2007;Rueping et al, 2007;Yamanaka et al, 2007), solid acids (Bigdeli et al , 2007 ;Li et al , 2007 ;Wang et al , 2007a,c ;Reddy et al , 2008 ), bases (Chandler et al , 2009 ;Wu et al , 2009 ), metal complexes (Wu et al , 2007a ;Wieland et al , 2009 ), ionic liquids (Dong et al , 2007 ;Fang et al , 2009 ), inorganic salts (Aryanasab and Saidi , 2008 ;Kidwai et al , 2008 ), and organic compounds (Verkade et al , 2008 ;Kano et al , 2009 ) as catalysts and many volatile organic solvents, some of which are hazardous for the environment. There are few reports on the use of heteroarylamines as substrates in the Mannich-type reactions (Shaabani et al , 2007 ;Hao et al , 2009 ).…”
Section: Introductionmentioning
confidence: 98%